(untitled) (Journal of Asian Development Studies, 2024)
This study critically analyzes disability and communal attitudes towards it across different societies throughout history. Existing literature has been extensively reviewed to understand disability in a historical context. The study demonstrates that disability has existed throughout human history, with societal responses shaped by cultural values and the prevailing mode of production. It reveals discrimination against persons with disabilities (PWDs) during the Greek and Roman periods, where disabled individuals were often deemed unfit for society. The emergence of capitalism exacerbated the marginalization of disabled people, relegating them to institutions. In contemporary society, persons with disabilities continue to face ableism and violations of their rights